THE SPORT EXERCISES AND THEIR IMPACT ON CARDIOVASCULAR SYSTEM (E Conference Zone, 2022)
The article reviews the presence of sport in the lives of people with diseases of the cardiovascular system. It was suggested options for alleviating the symptoms of heart disease through sports.